Analisis Perhitungan Muatan Sedimen Layang (Suspended Load) pada Muara Sungai Lilin Kabupaten Musi - Banyuasin - Rahma Diansari (Jurusan Teknik Sipil Fakultas Teknik Universitas Sriwijaya, 2014)
The river is a place or container and drainage networks ranging from the spring to the estuary with restricted right and left and all flow . The aim of this study was to quantify the sediment drift (suspended load ) that occurs in the mouth of the River Candles and comparing the calculation results with the results that were in the field. The research methodology used to calculate how much sediment is in the mouth of the wax by means of analyzing the data using the approach and Kalinske Lane , Einstein 's approach , and the approach Chang , Simons , and Richardson , so as to estimate how large the sedimentation in the estuary of the river due to the flow of the river . The results of the calculations for the discharge of sediment drift ( qsw ) on a piece of 1 ( STA 0 ) with Lane and Kalinske approach is 0.0107 ( kg / s ) / m , with Einstein's approach is 0.00457 ( kg / s ) / m , and with approach Chang , Simons , and Richardson is 0.000519 ( kg / s ) / m . While the 5 piece ( STA 4 ) the results obtained by Lane and Kalinske approach is 0.0102 ( kg / s ) / m , with Einstein's approach is 0.00679 ( kg / s ) / m , and with the approach of Chang , Simons , and Richardson value is 0.000696 ( kg / s ) / m . The results of the comparison with the calculation of sediment discharge drift field percentage obtained for the method of Lane and 40.78 % Kalinske pieces 1 ( STA 0 ) and 43.17 % 5 pieces ( STA 4 ) , for the method of Einstein by 74.61 % chunks 1 ( STA 0 ) and 62.28 % 5 pieces ( STA 4 ) , and for the method of Chang , Simons , and Richardson 97.12 % chunks 1 ( STA 0 ) and 99.61 % 5 pieces ( STA 4 ) . From the comparison of the percentage of sediment discharge hovering close to the ground is the result of using the Lane and by 40.78 % Kalinske pieces 1 ( STA 0 ) and 43.17 % 5 pieces ( STA 4 )Key Words : Sedimentation, Suspended Load, Lane and Kalinske approach, Einstein's approach, approach Chang , Â Simons , and Richardson approach .